Human Derived Dermal Fibroblasts as in Vitro Research Tool to Study Circadian Rhythmicity in Psychiatric Disorders - Palm, Denise; Uzoni, Adriana; Kronenberg, Golo; Thome, Johannes; Faltraco, Frank (Pharmacopsychiatry, 2023)
A number of psychiatric disorders are defined by persistent or recurrent sleep-wake disturbances alongside disruptions in circadian rhythm and altered clock gene expression. Circadian rhythms are present not only in the hypothalamic suprachiasmatic nucleus but also in peripheral tissues. In this respect, cultures of human derived dermal fibroblasts may serve as a promising new tool to investigate cellular and molecular mechanisms underlying the pathophysiology of mental illness. In this article, we discuss the advantages of fibroblast cultures to study psychiatric disease. More specifically, we provide an update on recent advances in modeling circadian rhythm disorders using human fibroblasts.
Keywords: human-derived fibroblasts; psychiatric disorders; sleep-wake rhythm disruptions; circadian genes